PENGUNGKAPAN KEPEMILIKAN MANAJERIAL, KEPEMILIKAN INSTITUSIONAL DAN CSR TERHADAP NILAI PERUSAHAAN PERTAMBANGAN YANG TERDAFTAR DI BEI TAHUN 2016-2018 - Sutrisno Sutrisno (JURNAL CAPITAL : Kebijakan Ekonomi, Manajemen dan Akuntansi, 2020)
Abstract. The purpose of this research is to find out. disclosure of managerial ownership, institutional ownership and CSR (Corporate Social Responsibility) to the value of mining companies listed on the Indonesia Stock Exchange 2016-2018. The population in this study were 24 mining companies. The variables in this study were managerial ownership of institutional ownership and CSR on firm value. Methods of data analysis using multiple linear regression, coefficient of determination and hypothesis testing.The results showed that the regression coefficient value of managerial ownership was 0.304, tcount (3.847)> t table (1.66) and sign (0.000), institutional ownership was 0.337, tcount (3.375)> t table (1.66) and sign (0.001) and CSR of 0.341, the value of tcount (4.110)> ttable (1.66) and sign (0.000), the coefficient of determination R2 is 62.8% in the F test of 38.231. This is managerial ownership, institutional ownership and CSR. has a positive and significant effect on firm value. Mining Company. mines that have disclosed managerial ownership and institutional ownership properly should carry out CSR activities. So that companies need to develop policies to guide implementation, this must be done so that the company's vision and mission can run well.